Influence of Return on Assets and Return on Equity on Price-to-Book Value, with Capital Adequacy Ratio as a Moderating Variable: A Study of Conventional Private Banks in Indonesia Listed on the Indonesia Stock Exchange During 2014–2023 - Jati, Lintang Permata; Pardistya, Irvan Yoga (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This research investigates how Return on Assets (ROA) and Return on Equity (ROE) influence the Price-to-Book Value (PBV), with the Capital Adequacy Ratio (CAR) acting as a moderating factor, using data from Indonesian private conventional banks over the period 2014 to 2023. Methodology: Utilizing a quantitative methodology and a descriptive-verificative framework, this study analyzes data sourced from the annual reports of banks listed on the Indonesia Stock Exchange. The analysis was carried out using multiple linear regression and moderated regression analysis (MRA), processed with IBM SPSS Statistics 26 software. Results: ROA and ROE have a significant effect on PBV. CAR moderates the relationship between ROA and PBV but does not significantly moderate the effect of ROE on PBV. Findings: Strong capital adequacy enhances the influence of profitability, especially ROA, on bank market valuation. Novelty: This study emphasizes the role of CAR in strengthening the impact of ROA on PBV within the post-pandemic banking environment. Originality: It provides insight into how market perception of profitability is shaped by capital strength in Indonesian private banks amid economic uncertainty. Conclusion: Effective management of assets, equity, and capital is essential to improve market perception and competitiveness. Type of Paper: Research Paper.